The Effects of Calcium Channel Antagonists on Coronary Nitrite Outflow in Isolated Rat Heart - Djuric, Dragan; Mitrovic, Veselin; Jakovljevic, Vladimir (Arzneimittelforschung, 2002)
The aim of the study was to compare the effects of Ca2+ channel antagonists on coronary endothelial L-arginine/NO system in isolated rat heart. The hearts of male Wistar albino rats (n = 36, age 8 weeks, body mass 180−200 g) were perfused according to Langendorff technique at gradually increased coronary perfusion pressure (CPP) which induced flow-dependent NO release (nitrite outflow). The experiments were performed during control condition or in the presence of different Ca2+ channel antagonists: nifedipine (CAS 21829-25-4, 30 nmol/l), diltiazem (CAS 42399-41-7, 3 µmol/l), verapamil (CAS 52-53-9, 0.4 µmol/l) or amlodipine (CAS 88150-42-9, 100 nmol/l) were administered separately. Also, nifedipine or amlodipine were administered in combination with an inhibitor of nitric oxide synthase (NOS), L-NAME (NG-nitro-L-arginine-methyl-ester, 30 µmol/l). Coronary flow (CF) varied in autoregulatory range from 3.93 ± 0.25 ml/min/g wt at 50 cmH2O to 4.49 ± 0.31 ml/min/g wt at 90 cmH2O. In autoregulatory range nitrite outflow varied from 1.80 ± 0.22 nmol/min/g wt at 50 cmH2O to 2.21 ± 0.25 nmol/min/g wt at 90 cmH2O and was strictly parallel with the CPP-CF (coronary perfusion pressure/coronary flow) curve. The autoregulatory range of CF was significantly extended (40−100 cmH2O) under the influence of nifedipine. Hemodynamic effects were accompanied by significant changes in nitrite outflow in all groups except for the verapamil group. Nifedipine and diltiazem induced statistically significant increases of nitrite outflow in coronary venous effluent, strictly parallel with the CPP-CF curve, from 58 % at 120 cmH2O to 190 % at 40 cmH2O and from 74 % at 120 cmH2O to 166 % at 40 cmH2O, respectively. On the contrary, amlodipine induced significant reduction of nitrite outflow which was stronger at the lower value of CPP (44−46 % at 40−80 cmH2O), compared to the higher value of CPP (32−37 % at 100−120 cmH2O). When L-NAME was applied in combination with nifedipine or amlodipine, CF was significantly reduced with parallel changes in nitrite outflow. The results show that Ca2+ channel antagonists (verapamil, diltiazem, nifedipine and amlodipine) strongly influence the coronary endothelial L-arginine/NO system in isolated rat heart leading to the difference in nitrite outflow.
Keywords: Amlodipine; Ca2+ channel antagonists, effects on endothelium, effects on nitrite; outflow, rat heart; CAS 52-53-9; CAS 21829-25-4; CAS 42399-41-7; CAS 88150-42-9; Diltiazem; Nifedipine; Verapamil